`I'd rather go and know': women's understanding and experience of DEXA scanning for osteoporosis - Richardson, Jane C. (Health Expect, 2002)
Objective  To explore women's knowledge and understanding of osteoporosis and of dual energy x‐ray absorptiometer (DEXA) scans; the factors influencing their decision to have a scan and their experience of undergoing a DEXA scan. Design  In‐depth interviews (using a topic guide) were carried out with 12 women [before a DEXA scan and after they had discussed the results with their general practitioner (GP)] and with three women who chose not to have a scan. Setting  Stoke‐on‐Trent, Staffordshire, UK. Participants  Women who responded to a primary‐care based questionnaire were purposively selected for interview. Results  The women interviewed had varied levels of understanding of osteoporosis. For the majority of participants the scan was an overwhelmingly positive experience, despite some women's negative expectations. Findings are also explored in terms of the influences on women's decision‐making about whether to have a scan and the concept of `knowing' one's risk status. Conclusions  The main implication for primary care is how to improve women's understanding of osteoporosis and DEXA scans in order to promote the strategy of scanning high‐risk women.